2015
DOI: 10.4103/2249-4863.174295
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic role of ischemia modified albumin and high-sensitivity troponin T in the early diagnosis of acute coronary syndrome

Abstract: Aim:The aim was to evaluate the role of high sensitivity troponin T and ischemia modified albumin (IMA) and in the early diagnosis of acute coronary syndrome (ACS).Materials and Methods:This was a cross-sectional study that comprised of 120 individuals of which 75 were cases and 45 healthy controls. On the basis of clinical history and 12-lead electrocardiogram, initial diagnosis of ACS was made in the cases. High sensitive cardiac troponin T (hs-cTnT) and IMA were measured in all the individuals.Results:Level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…In patients with suspected ACS, the diagnostic accuracy at presentation increased when IMA was used in conjunction with cTnT and ECG findings 25. In fact, IMA in combination with initial cTnT is more sensitive than the latter alone for predicting adverse cardiac events, although the specificity and sensitivity for IMA are too low to be useful for clinical decision-making 26…”
Section: Summary Of Cardiac Biomarkersmentioning
confidence: 99%
“…In patients with suspected ACS, the diagnostic accuracy at presentation increased when IMA was used in conjunction with cTnT and ECG findings 25. In fact, IMA in combination with initial cTnT is more sensitive than the latter alone for predicting adverse cardiac events, although the specificity and sensitivity for IMA are too low to be useful for clinical decision-making 26…”
Section: Summary Of Cardiac Biomarkersmentioning
confidence: 99%
“…Once these free radicals in local myocardium increased, an increase in IMA would be subsequently induced. [ 13 , 18 – 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…IMA concentration rapidly increased in 5 to 10 minutes postmyocardial ischemia in peripheral blood, and sustained increase during the course of ischemia, it would lasted for 2 to 4 hours, and returned to baseline level in 6 to 10 hours. [ 11 , 12 ] Since it can be detected in the reversible phase of myocardial injury, and possesses the advantages of high sensitivity, high negative predictive value and early appearing, [ 13 ] it has become a hot topic in clinical research.…”
Section: Introductionmentioning
confidence: 99%
“…In acute ischemia, the N-terminal end of albumin is damaged, reducing its ability to bind. It has been used in several studies that have shown its usefulness in the diagnosis of acute coronary syndromes in conjunction with tropine values and ECG changes [ 52 ]. It has been shown that this combination of biomarkers (troponin and modified albumin) has a predictive value higher than any of them taken separately [ 53 ].…”
Section: Biomarkersmentioning
confidence: 99%